The Influence of Children's Singing on Listening and Speaking Skills at the Methodist Playgroup in North Jakarta - Widiati, Debora Pujo; Puridawaty, Brigita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to identify the effect of children's singing on listening and speaking skills in playgroup children at KB Methodist North Jakarta. The focus of the study was on children aged 3-4 years. This study was conducted because, in the Methodist Playgroup, several children were found to be lacking in listening skills and not yet fluent in speaking. The method used was quantitative analysis, with an experimental model, which tested the effect of children's singing on listening and speaking skills. From the results of the study, it showed that the application of children's singing had a significant effect on listening and speaking skills, with a significance value of 0.000 which was smaller than α = 0.05, so that the hypothesis in this study was accepted.